HUBUNGAN ANTARA JARAK KELAHIRAN DENGAN PERILAKU SIBLING RIVALRY PADA ANAK USIA PRA SEKOLAH (4-6 TAHUN) - Siti Muniroh (Wiraraja Medika : Jurnal Kesehatan, 2017)
The presence of a brother will contribute to social and emotional development of a child, andalmost never be able to avoid the sibling rivalry or sibling rivalry. Sibling rivalry behavior is causedby several factors: internal and external factors.The purpose of this study was to find out is there arelationship between birth spacing behavior of sibling rivalry in preschool children (4-6 years) in TKPerwanida Jombatan Jombang.This type of research is a descriptive analytic cross sectional approach. The population in thisstudy of 40 children and the number of samples is 30 children selected by purposive samplingtechnique. The variables measured were birth spacing as an independent variable, while thedependent variable behavior of sibling rivalry in preschool children (4-6 years).Results obtained from this study almost half of the spacing of 2-4 years category at 46.7%while the behavior of most of sibling rivalry is there a category of 60%. Statistical tests used in thisstudy is the Spearman rank test statistic 0.01 there is spacing relationship to the behavior of siblingrivalry in preschool children (4-6 years) in TK Perwanida Jombatan Jombang.The very importanceof estimating the distance between the child's birth with one another in order to avoid sibling rivalrybehavior.